The epistle of Paul to the Romans an introduction and commentary - Bruce, Frederick Fyvie, 1910-90 (London, UK Tyndale, 1963)
Includes bibliographical references.
Brethren writer
Keywords: Bible. N.T. Romans -- commentaries